2004
DOI: 10.1002/jctb.1165
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydrolysis under anaerobic, saline conditions in presence of acetic acid

Abstract: The hydrolysis of soluble proteins in an anaerobic, saline (24 g dm −3 NaCl) and mesophilic (37• C) environment was studied. The inhibitory effect of a volatile fatty acid, acetic acid (HAc), on the hydrolysis rate and hydrolytic biomass activity for a model saline wastewater with a high protein load (total organic carbon, 1153 mg dm −3 and 1572 mg dm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…However, 20 g/L of acetate inhibited carbohydrate hydrolysis by 30%, which value did not agree with those obtained by or Babel et al (2004) without inhibition. The inhibitions by pH or VFA on protein hydrolysis were similar to those reported by González et al (2005).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, 20 g/L of acetate inhibited carbohydrate hydrolysis by 30%, which value did not agree with those obtained by or Babel et al (2004) without inhibition. The inhibitions by pH or VFA on protein hydrolysis were similar to those reported by González et al (2005).…”
Section: Discussionsupporting
confidence: 87%
“…Zou et al (2003) and , observed the decline in hydrolysis rate of biowaste caused by the accumulation of VFA. González et al (2005) found that the hydrolysis of soluble protein was completely inhibited at a concentration of acetate of over 1,000 mg/L. Anaerobic Digestion Model No.1 (ADM1) revealed that pH could inhibit hydrolysis, if required (Batstone et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Acetic acid was the dominant VFA observed in this study, followed by propionic and butyric acid. VFAs could be generated from hydrolysis and anaerobic digestion of carbohydrates (Babel et al, 2004;Gonzalez et al, 2005), fats, and proteins present in the waste and could accumulate when inadequate oxygen was supplied during aerobic biodegradation (Nicolas, 2006).…”
Section: Predominant Compoundsmentioning
confidence: 99%